Achondroplasia and Biliary Atresia: A Rare Association and Review of Literature - Kylat, Ranjit I. (Journal of Pediatric Genetics, 2017)
Achondroplasia (ACH) occurs in most cases as de novo mutations of the gene-encoding fibroblast growth factor receptor 3 (FGFR3). Biliary atresia (BA) is a progressive neonatal inflammatory and fibro-obliterative cholangiopathy affecting the extra- and intrahepatic biliary tree to varying degrees, and it results in obstruction to bile flow and cholestatic jaundice in neonates. BA is thought to be a multifactorial disease, genome association studies have shown abnormalities in susceptibility genes, and levels of fibroblast growth factor 21 (FGF21) and fibroblast growth factor 23 (FGF23) have been noted to be increased. These two conditions occurring in the same patient has never been reported before.
Keywords: biliary atresia; achondroplasia; skeletal dysplasia; fibroblast growth factors; fibroblast growth factor 21; fibroblast growth factor 23; fibroblast growth factor receptor 3; glypican 1